STUDENT RESPONSES IN LEARNING INQUIRY MODEL INTEGRATING ARCS MOTIVATION STRATEGY ON ACID-BASE MATERIALS - Maria Benedikta Tukan; Faderina Komisia (JCER (Journal of Chemistry Education Research), 2017)
The purpose of this research was to describe the response of grade XI students of SMAK Saint Carolus Kupang in the learning that integrated the ARCS motivation strategy in the inquiry model on the acid-base materials. This type of research is quasy experiment design. This research was conducted at SMAK Saint Carolus Kupang, East Nusa Tenggara. The design of this research using Nonequivalen Control Group Design. The instrument in this research is using student response questionnaire. The data collection procedure in this research is questionnaire. The result of his research is that the students' responses in learning that integrate ARCS motivation strategy in inquiry model is good.